Pelaksanaan Penyidikan Penyidik Pegawai Negeri Sipil Dinas Tenaga Kerja Dan Transmigrasi Prov.Sulsel Terhadap Pelanggaran Ketenagakerjaan - Udin Palamma; Hartono Hamzah; Wahyu Rasyid; Asrul Hidayat (Fakultas Hukum Dehasen, 2026)
This study aims to study and analyze (1) How is the implementation of investigation by investigating civil servant employment for violation of labor laws, (2) whether the constraints experienced by the civil servant investigator in the field of employment against labor violations. The method used is descriptive and includes views of objective empirical research. Research sites in manpower and transmigration sulsel.htm province, police Sulselbar, Reported (Entrepreneur), Rapporteur (Workers). Data used include primary data and secondary data. Techniques of data collection through interviews, questionnaires and distribute both the research literature books, legislation, papers, results of previous studies, documents, and so on. Analysis of the data using qualitative analysis.Based on this study, the investigation result that implementation of labor law violations committed by employment investigators conducted under the provisions of the Criminal Procedure Code which governed most of the violators of labor laws that are subject to sanctions of administrative actions. Perpetrators of violations of labor laws are examined and sentenced by the court, the amount is very little. Constraints are related to the budget allocation is still inadequate, human resources are not sufficient, in terms of both quality and quantity, investigators are still attached to the work areas / activities. have good coordination between police and prosecutors. And the need for centralized with the central government investigators. The solution should be given priority in the budget to support the provision of law enforcement duties by labor investigators. In order to improve the quality, ability and integrity of the investigators, investigators need all called to follow the development of quality education and comprehensive standards. To increase the motivation of labor investigators, need to be given as well as the functional benefits to them. Coordination that is horizontal with the prosecutor agencies should be improved, in order to avoid return of the case file until a few times. Investigators should be centralized so that employment is not easy to be intervened by the leader/ head area.